Sustainable Strategies for Improving Humanitarian Supply Chain Management in the United Nations Using Dynamic Capability Theory - Mirjana Mazar; Kenneth Gossett; Manish Shashi (Standards)
The purpose of the qualitative multiple case study was to explore the strategies some supply chain managers of the United Nations (UN) use to leverage operational efficiencies in the UN humanitarian programs. As a result, communities supporting sustainability and peace or those fostering economic development will be able to respond effectively to humanitarian crises. Moreover, the UN can remain operational and engage in political and conflict-reduction interventions integral to economic and social recovery and sustainability. This study applied the qualitative multiple case study through semi-structured interviews with nine supply chain managers in the United Nations, direct observations, document analysis, and artifacts. The research is grounded in the dynamic capability theory (DCT). The research revealed several strategies that supply chain managers of the UN use to ensure operational efficiencies grouped around three themes: (a) analytical, innovation, and knowledge management strategies; (b) effective supply chain management leadership strategies; and (c) risk management strategies. This study is one of the first to apply generic findings of humanitarian supply chain studies to the United Nations, the global organization with diverse mandates that continuously strives to achieve efficiencies required by donors providing financial support, thus remaining operational. The study’s results could help leaders in the various humanitarian organizations who operate in vulnerable environments and under strict scrutiny from donors to deliver their aid programs most efficiently by understanding dynamic capabilities. Previous studies indicate the lack of strategic frameworks applicable to the United Nations that could improve decision-making at the strategic, tactical, and operational levels, facilitate collaboration among supply chain stakeholders, and reduce the costs of the operational performance of the supply chain system in the UN.